Industial symbiosis in a circular economy:towards firms' sustainable competitive advantage - Lopes, João (2019)
The main objective of this article is to provide a comprehensive view of academic studies that address simultaneously the circular economy and industrial symbiosis, based on bibliometric data for the years 1900 to 2018. Data are collected in Web of Science using the VOSviewer software. Bibliometric indicators, network citation, cluster analysis, and density view analysis are used. From our findings we highlight four clusters in the research, which help to contextualize the literature review: (a) circular economy: approaches and tools; (b) industrial symbiosis Dynamics; (c) circular economy: strategies and performance; (d) the efficiency of resources in symbiosis industry. This study also establishes perspectives for future lines of research and, correspondingly, seeks to provide a theoretical basis that can serve as a starting point for future studies.